Lantana Lace Bug, Teleonemia scrupulosa Stål (Insecta: Hemiptera: Tingidae) - Dale H. Habeck; Frank W. Mead; Thomas R. Fasulo (EDIS)
The lantana lace bug, Teleonemia scrupulosa Stål, often causes extensive damage to lantana, Lantana camara L. Although lantana is sometimes used as an ornamental, it is usually considered a weed. It often forms spiny, dense, impenetrable thickets covering large areas of valuable land. The lantana lace bug has been introduced into many countries as a biological control agent to combat lantana. This document is EENY-246 (originally published as DPI Entomology Circular 156), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2001.